Research on Safety Risk Evaluation System for Seepage in Ship Lock Foundation Pit Engineering - Jianhong Huang; Jian Xie; Honglei Ren (Buildings)
Ship lock project currently demonstrates a distinct cyclical pattern, accumulating latent hazards that pose a significant threat to project safety. Seepage safety (the condition in which the seepage risk is reduced to an acceptable level) serves as a crucial indicator in the safety risk assessment index system for ship lock project construction, thus necessitating an in-depth analysis of the risk factors impacting seepage safety. Utilizing a ship lock project in China as a case study, this study employs the finite element method (FEM) to analyze the seepage field of the ship lock foundation pit basin and proposes a comprehensive set of methods for risk evaluation and warning models pertaining to seepage safety risks in ship lock engineering. This study reveals that the obstruction of dewatering wells and imperfections in the diaphragm wall are the primary factors contributing to seepage damage. The investigation conducted a quantitative analysis of the impact of these two factors on the seepage field of the ship lock pit, considering pore pressure, water head, gradient, and flow velocity. A comprehensive set of evaluation indicators for seepage safety was formulated, drawing on the principles of multi-objective optimization, and a method for delineating the safe range of ship lock pit excavation under seepage action was proposed. Subsequently, an integrated seepage safety risk assessment system for ship lock pit excavation engineering was established. These research findings offer a scientific foundation for the management of seepage safety in ship lock pit excavation engineering and provide valuable references and guidance for the development of anti-seepage systems.